If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 9h = 8h Solving -9 + 9h = 8h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-8h' to each side of the equation. -9 + 9h + -8h = 8h + -8h Combine like terms: 9h + -8h = 1h -9 + 1h = 8h + -8h Combine like terms: 8h + -8h = 0 -9 + 1h = 0 Add '9' to each side of the equation. -9 + 9 + 1h = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 1h = 0 + 9 1h = 0 + 9 Combine like terms: 0 + 9 = 9 1h = 9 Divide each side by '1'. h = 9 Simplifying h = 9
| 0.72=3.5 | | 2(16+y)=32+34y | | 9(3-16)+15=6x-24 | | 17/9=8/9y | | 5x+11=9x+19 | | X/12-1/4=5/3 | | -4(1-4p)= | | 7c-28=-7 | | 2x=42-20 | | 10r^2-17r=6 | | 9x(x-5)=(2x+1)(9x-5) | | -4+16p= | | ((18*5)-50/2=x | | x+(-0.9)=(-4.9) | | 3/5x-7=4 | | y+y=16 | | 2x+6-7= | | -10v-20=-70 | | m+4=-3 | | D=KQ | | -4^2-52/6-9 | | 13n-84=4n-3 | | 4n+32=56 | | 8(6-n)=88 | | 4*8y= | | 17+m=5 | | 19+b=11 | | -0.3+(-2.8)=-4 | | X^2-12x-33=0 | | -5m+7(-3m+4)=106 | | 0.2+0.35+0.0037= | | W-72=36 |